The Development of a Digital-Based Attendance System to Enhance the Discipline of Fifth Grade Students at SD Negeri 62 Palembang - Sari, Nurul; Harapan, Edi; Indrawati, Sri Wahyu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The integration of digital technology in education is increasingly recognized as a strategic effort to support character development and improve student discipline. This study explores the development and implementation of a digital-based attendance system to enhance the discipline of fifth-grade students at SD Negeri 62 Palembang. Employing a research and development (R&D) approach based on the Borg and Gall model, this study involved stages from preliminary research to product refinement. The digital attendance system utilizes barcode technology, allowing real-time and automated recording of student attendance. In the context of Indonesian elementary education, the use of barcode-based attendance represents a novel and practical innovation, addressing long-standing challenges of manual record-keeping and promoting digital literacy among students and teachers alike. Data were collected through expert validation questionnaires, user practicality assessments by teachers and students, and discipline observations. Quantitative analysis revealed that the developed product was highly valid, with expert approval ratings indicating strong content and media reliability. The practicality test showed 98% of teachers and 100% of students responded favorably. Effectiveness was evaluated through pretest and posttest assessments of student discipline, supported by statistical analysis using the Wilcoxon Signed-Rank Test and Mann-Whitney U Test, both showing significant improvements in the experimental groups (p = 0.000). These findings demonstrate that digital attendance systems can significantly increase student punctuality and overall discipline. This study contributes to the growing literature on educational technology adoption in elementary schools and provides practical insights for schools seeking innovative digital solutions to support character education and school management.